Teknologi Tepat Guna dan Penambahan Alat Produksi untuk Meningkatkan Produktivitas Usaha Bolu Labu - Made Satria Wibawa; Nyoman Ayu Nila Dewi; Ni Luh Putu Ririn Trisnayanti (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2020)
The home industry for food has now begun to develop, seeing so many types of cakes and snacks that sell products to traditional markets. This internal community service activity will carry out community service activities for internal community service activities. Existing requirements where the use of partner equipment is still quite minimal while the oven used is still quite small with 1 baking capacity. The level of understanding of partners in the use of technology is still very minimal by looking at the low promotion and marketing media carried out by partners. The current partner marketing process is entrusted to traditional markets around the partner location. Other marketing is done by entrusting products in schools in partner locations. Products that are partnered by partners do not contain the packaging labels and business partner information. From these problems, the internal community service activities will provide assistance in the form of an oven with a capacity of 3-4 oven baking pan to improve the production process. Providing packaging labeling training to enhance partners' knowledge of the use of technology. Training in the use of technology using online marketing media. Utilization of this technology is used to market products produced through online media.